(untitled) (The Review of Diabetic Studies, 2024)
Out-of-hospital cardiac arrest (OHCA) remains one of the most critical and time-sensitive emergencies in global medicine, with survival outcomes heavily dependent on the speed, coordination, and continuity of care delivered across prehospital and in-hospital settings. Despite major advances in emergency medicine and resuscitation science, survival-to-discharge rates for OHCA remain low worldwide, averaging between 7% and 10%, with significant regional variation depending on emergency medical system maturity and post-resuscitation care quality. This review presents a comprehensive analysis of the integrated multidisciplinary approach required for optimizing survival and neurological outcomes in OHCA. The model emphasizes collaboration among emergency physicians, family physicians, paramedics, patient care technicians, and healthcare informatics professionals. It explores how coordinated systems of care—anchored in rapid prehospital response, evidence-based hospital management, data-driven feedback, and community reintegration—can improve patient outcomes while aligning with global initiatives and Saudi Vision 2030 healthcare transformation strategies.